Optimizing Digital Communication in Dealing with Cybercrime for the Visually Impaired - Nurani Muksin, Nani; Yuningsih, Siska; Rosmi, Fitria; Pirmansyah, Khalid (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The advancement of digital technology in the cyber era has opened up wide access to information, communication, and digital services. However, this progress has also given rise to challenges in the form of increasing cybercrime targeting vulnerable groups, including people with visual sensory disabilities. Limitations in receiving visual information make this group more vulnerable to threats such as phishing, theft of personal data, and digital fraud. In response to this, a community service activity entitled